Effet antimicrobien des extraits de Mentha x piperita sur Escherichia coli responsable dans les infections urogénitales chez les femmes - Belghit, Samira; Djilidjel, Hamida (My University, 2018)
This work investigated the effect of extracts with hexane, methanol, ethanol and peppermint water (Mentha x piperita) harvested in the Mostaganem and Naama regions on one of the most responsible germs for urogenital infections in women namely Escherichia coli. The extraction of the bioactive compound was carried out from the aerial part of the plant.The extracts obtained were diluted to 20, 40, 60, 80 and 100%. The measurements and controls were carried out in triple trials and concerned (the direct contact method, the disk diffusion method, the MIC and the MBC). The hexane extract, the least polar, seems to have the best antimicrobial effect in E. coli; with low growth rates and very high inhibition rates. The survival rate is zero for Mostaganem peppermint extracts prepared at 20, 40, 60 and 100%.however, Naama extracts with hexane and water showed an MIC of 80%; and with the methanolic extract prepared at 60% and the ethanolic extract at 20%. The MBC peppermint extracts collected at Mostaganem were obtained from E.coli at 100% pure ethanol and aqueous extractions and with the 20% hexane extract and 80% methanol extract. Regarding the extracts of peppermint from Naama, the E.coli MBC is made with pure hexane and water extracts of 100%, as well as with the methanol extracts of 60% and 20% ethanol. Solvent extracts with different polarities of Mentha x piperita from both study regions appear to exert a bactericidal effect in Escherichia coli.
Keywords: Mentha x piperita; Escherichia coli; Extract; Antimicrobial activity; Inhibitor; MIC; MBC; Mentha x piperita; Escherichia coli; Extrait; Activité antimicrobienne; Inhibiteur